Efektivitas Pelatihan Karyawan dalam Mengurangi Reject Produk : Studi pada Perusahaan Manufaktur Alat Peraga Pendidikan - Muhamad, Haekal; Endang Silaningsih (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the implementation and effectiveness of employee training in reducing product reject rates at PT PDN. The research employs a qualitative descriptive approach with data collection techniques including observation, in-depth interviews, discussions, and documentation. The findings indicate that employee training has not been implemented optimally, as reflected in low participation levels, incomplete program execution, misalignment between training materials and operational needs, and limited variation in training methods. These conditions have negatively affected employees’ technical competencies, increased product reject rates, and hindered the achievement of production targets. This study recommends the development of training programs based on job needs analysis, the application of practical and interactive training methods, flexible scheduling, and continuous evaluation to enhance training effectiveness, employee performance, and product quality sustainably as a strategy to strengthen the long-term competitiveness of manufacturing companies at both national and global levels.